GM-CSF in murine psoriasiform dermatitis: Redundant and pathogenic roles uncovered by antibody-induced neutralization and genetic deficiency. - Tatjana Scholz; Andreas Weigert; Bernhard Brüne; Christian D Sadik; Beate Böhm; Harald Burkhardt (PLoS ONE)
Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a pleiotropic, Th17-derived cytokine thought to critically contribute to the pathogenesis of diverse autoimmune diseases, including rheumatoid arthritis and psoriasis. Treatment with monoclonal antibodies that block GM-CSF activity is associated with favorable therapeutic effects in patients with rheumatoid arthritis. We evaluated the role of GM-CSF as a potential target for therapeutic interference in psoriasis using a combined pharmacologic and genetic approach and the mouse model of imiquimod-induced psoriasiform dermatitis (IMQPD). Neutralization of murine GM-CSF by an anti-GM-CSF antibody ameliorated IMQPD. In contrast, genetic deficiency in GM-CSF did not alter the course of IMQPD, suggesting the existence of mechanisms compensating for chronic, but not acute, absence of GM-CSF. Further investigation uncovered an alternative pathogenic pathway for IMQPD in the absence of GM-CSF characterized by an expanded plasmacytoid dendritic cell population and release of IFNα and IL-22. This pathway was not activated in wild-type mice during short-term anti-GM-CSF treatment. Our investigations support the potential value of GM-CSF as a therapeutic target in psoriatic disease. The discovery of an alternative pathogenic pathway for psoriasiform dermatitis in the permanent absence of GM-CSF, however, suggests the need for monitoring during therapeutic use of long-term GM-CSF blockade.